Examining Professional Development among Faculty Members across Varying Career Stages in Kinesiology. (2nd January 2022) - Muir, Irene L.; Chittle, Laura; Santarossa, Sara
ABSTRACT: Professional development (PD) was examined among faculty members to identify enablers and inhibitors, and the coping strategies used to mitigate these. Three faculty members in the field of Kinesiology, at different career stages (early, middle, and late career), were recruited to participate in semi-structured phone interviews. Guided by Cafarella and Zinn's (1999) conceptual framework, four domains of PD were explored. Key PD enablers were mentorship, geographic isolation, scarce teaching resources, and limited financial support. The use of problem-focused and emotion-focused coping was also reported. Implications for post-secondary faculty and administration are presented.